Recenzió A gazdaságszociológia kézikönyve című kötetről : Smelser, N.J. and Swedberg, R. eds.: The Handbook of Economic Sociology. Princeton–Oxford/New-York: Princeton University Press/Russel Sage Foundation, 2005. - Ercsei, Kálmán; Gál, Katalin; Simon, Boglárka; Szathmári, Milán; Szél, Bernadett (Szociológiai Szemle, 2024)
-